Caracterização de poli(m-fenileno isoftalamida) modificado com 2-iodo-1-etanol. - Santos, Sandra Cruz dos (2010)
Poly(m-phenylene isophthalamide) an aromatic polyamide, belong to an important class of polymers which, in the last decades, have called attention of many research groups. This fact is justified not just by the high performance of this material, but, also, by its unique physical chemical behavior. The excellent thermal stability and chemical stability is responsible for its use as thermal and electrical insulator. The difficulty of processing is due the high glass transition temperature, crystallinity and chemical inertia. Few systems as N,N-dimethylformamide (DMF) with 5% w/V LiCl, are able to dissolve this polymer. In this work, the polymer was treated with dimsyl sodium ion and posterior reaction with 2-iodine-1-ethanol. The NH hydrogen substitution by the alcohol group was 56% and was confirmed through infrared and magnetic resonance techniques. The modified polymer present pink color, decrease of molecular weight and is amorphous up to 400 °C and presents thermal stability similar to the unmodified polymer. The improvement of the solubility rate is observed and the substituted material is soluble in DMF with lower concentration of LiCl (1.5%). It can be observed two different behaviors in solution. At concentrations higher than the critical aggregation concentration (cac), viscosity and relaxation times increase with concentration. At concentrations lower than cac, the viscosity and relaxation time decrease with increasing of concentration. This fact can be explained by the capacity of the polymer modify the ionic strength of the media.